1993
DOI: 10.7326/0003-4819-119-4-199308150-00002
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Lipoprotein(a) in Patients with the Nephrotic Syndrome

Abstract: Most patients with the nephrotic syndrome have Lp(a) concentrations that are substantially elevated compared with controls of the same apo(a) isoform. Because Lp(a) concentrations are substantially reduced when remission of the nephrotic syndrome is induced, it is likely that the nephrotic syndrome results directly in elevation of Lp(a) by an as yet unknown mechanism. The high levels of Lp(a) in the nephrotic syndrome could cause glomerular injury as well as increase the risk for atherosclerosis and thrombotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
1
2

Year Published

1995
1995
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(73 citation statements)
references
References 0 publications
7
63
1
2
Order By: Relevance
“…The mean Lp(a) value in nephropathy cases was 46.3 __17.6 mg/dl which were significantly raised (p<0.001) when compared to non nephropathy cases and controls. Similar findings were reported by Haffner et al (1992) Warner et al (1993), Geethanjali F.S., 1999, who showed that Lp(a) levels did not differ significantly between diabetics and controls but increased levels were seen in patients with proteinuria and diabetic nephropathy (13,14,15).…”
Section: Discussionsupporting
confidence: 85%
“…The mean Lp(a) value in nephropathy cases was 46.3 __17.6 mg/dl which were significantly raised (p<0.001) when compared to non nephropathy cases and controls. Similar findings were reported by Haffner et al (1992) Warner et al (1993), Geethanjali F.S., 1999, who showed that Lp(a) levels did not differ significantly between diabetics and controls but increased levels were seen in patients with proteinuria and diabetic nephropathy (13,14,15).…”
Section: Discussionsupporting
confidence: 85%
“…In subjects with IDDM and proteinuria, Lp(a) levels have been reported to be either increased or unchanged [31,[42][43][44][45][46][47]. Several studies of patients with nephrotic syndrome and/or renal failure from various causes have failed to demonstrate a difference in Lp(a) levels in subjects with IDDM compared with in subjects with other causes of renal dysfunction [20,29,65]. In the present study, most of the subjects had a normal creatinine clearance (greater than 1.17 ml [bullet] s sup-1 [bullet] 1.73 m sup-2) and level of albuminuria (less than 40 mg/24 h).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher cholesterol levels are present in the more buoyant LDL fractions (fractions 12-18) of the intensively treated group. A trend can be seen toward lower cholesterol content in the intermediate-density lipoprotein (IDL) fractions (fractions [19][20][21][22][23][24][25][26][27][28][29][30] in the intensively treated group, although this did not reach statistical significance.…”
Section: Dgucmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 For instance, modifications in the levels of plasminogen may be related to age, in view of the fact that low levels have been found in nephrotic children 7,8 and normal or increased levels have been found in nephrotic adults. 9,10 In contrast, increased concentrations of Lp(a), the lipoprotein particle containing apo(a), a glycoprotein genetically related and structurally homologous to plasminogen, have been reported in nephrotic adults 9,[11][12][13] and in children. 14,15 Because high plasma levels of Lp(a) are now recognized as a risk factor in cerebrovascular and cardiovascular diseases, 16 -18 increased concentrations of Lp(a) may represent an added thrombotic risk in nephrotic subjects.…”
mentioning
confidence: 99%